1995
DOI: 10.1016/0014-5793(95)01126-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytochrome P450 CYP1B1 in breast cancer

Abstract: The expression of CYP1B1 has been identified in breast cancer using the reverse transcriptase-polymerase chain reaction and immunoblotting. CYP1B1 mRNA was expressed in the majority of breast tumours and immunoblotting of breast tumours identified a single protein band of molecular weight 60 kDa corresponding to the predicted molecular weight of human CYP1B1. This is the first study to identify CYP1B1 expression in a turnout where it may represent a previously unknown pathway for the metabolism of oestradiol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 20 publications
6
63
0
Order By: Relevance
“…Higher levels are found in a wide range of human cancers including cancers of the skin, brain, testis (85) and breast (86). CYP1B1 converts oestrogen to 4-hydroxylated metabolites (87) that may initiate breast cancer in humans (88). The enzyme also plays an important role in activating diverse procarcinogens including PAHs, aryl and heterocyclic amines and nitroarenes to reactive metabolites that cause DNA damage (Table 1) (89,90).…”
Section: Cyp1b1mentioning
confidence: 99%
“…Higher levels are found in a wide range of human cancers including cancers of the skin, brain, testis (85) and breast (86). CYP1B1 converts oestrogen to 4-hydroxylated metabolites (87) that may initiate breast cancer in humans (88). The enzyme also plays an important role in activating diverse procarcinogens including PAHs, aryl and heterocyclic amines and nitroarenes to reactive metabolites that cause DNA damage (Table 1) (89,90).…”
Section: Cyp1b1mentioning
confidence: 99%
“…COMT has a higher affinity for 2-OHE 2 over 4-OHE 2 , resulting in an increased genotoxicity of the 4-OHE 2 metabolite (Tsuchiya et al 2005). High concentrations of 4-OHE 2 metabolites have been associated with human breast cancers (Rogan et al 2003), and elevated CYP1B1 mRNA transcripts have been identified in many cancerous tissues including breast, testis, and ovary (McKay et al 1995, Murray et al 1997 suggesting that elevated levels of CYP1B1-mediated E 2 metabolism can lead to carcinogenesis. 2-OHE 2 metabolites appear to be tumor inhibitors (Tsuchiya et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although CYP1B1 expression has been observed in multiple cancers examined to date (colon, lung, renal, bladder, and glaucoma), it shows particularly high expression in many of the hormone-mediated cancers (prostate, breast, endometrial, and ovarian; refs. 5,11,12). CYP1B1 is also implicated in the etiology of hormone-mediated tumors, as it is responsible for hormone metabolism and the formation of toxic metabolites from both endogenous and exogenous molecules (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%